(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Wireless nodes share one common channel and the access is governed by binary exponential back off procedure by default. Because of its limited capacity, the MANETs are very sensitive to overhead packets. If the bandwidth available is not correctly determined, nodes must accept additional QoS requests and overloading of the network must result. To increase the bandwidth available and to reduce the overhead control correlated with the back-off scheme used in the MAC (Medium Access Control) layer pipelined dea is applied to back off procedure. Pipelined process reduces the data channel contention so that collision probability is reduced. It is essential to perform routing with maximal throughput and with minimal control overhead. The proposed algorithm is incorporated into the multi-path routing protocol called the enhanced link multipath disjoint AODV(ADHOC On-demand Distance Vector) that allows multiple paths to be established between a single source and a single destination node. Multiple routes to increase the effective bandwidth of contact pairs, respond to congestion and bursty traffic, high mobility and increasing reliability. This approach is implemented in NS2 simulator. Performance of this method is evaluated in terms of throughput, packet delivery ratio, effective bandwidth utilization, energy consumption.